1991
DOI: 10.4037/15597768-1991-3008
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Concerns of the Ventilator-dependent Child in the Pediatric Intensive Care Unit

Abstract: An increasing number of infants and children suffer from respiratory and neuromuscular diseases that render them ventilator-dependent. These patients spend months in pediatric intensive care units (PICUs) until they are either extubated or are stable enough to tolerate home ventilation. The critical nature of the PICU and its emphasis on meeting short-term goals is not readily compatible with the long-term and dynamic needs of developing children. In order to prevent the delays in growth and development that o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…These facilities not only provide skilled nursing care to this high-risk population but can also provide respite care and rehabilitation activities for the children and families to participate in together. 19,[26][27][28] Arguably, the creation of such facilities has made it more plausible for patients with higher ventilator settings who may be less appropriate for home disposition to leave the hospital setting. The discovery that higher settings were used in those subjects going to such facilities may support this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…These facilities not only provide skilled nursing care to this high-risk population but can also provide respite care and rehabilitation activities for the children and families to participate in together. 19,[26][27][28] Arguably, the creation of such facilities has made it more plausible for patients with higher ventilator settings who may be less appropriate for home disposition to leave the hospital setting. The discovery that higher settings were used in those subjects going to such facilities may support this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…There are considerable psychological and developmental disadvantages to long term hospital based care 56 Increasing emphasis is being placed on measures to transfer these children home 7. Appropriate medical equipment exists for home care but, in spite of the considerable psychosocial and financial benefits of home mechanical ventilation, the discharge process is often fraught with difficulties.…”
Section: Mission Statementmentioning
confidence: 99%
“…They emotionally mature through distinctive experiences such as living with a life threatening condition since birth or living through a traumatic accident ( Gorman et al ., 1998 ). There is an extensive literature that describes the intensive care unit as an unsuitable environment for the awake and alert child (for example Tichy et al ., 1988 ; Kidder, 1989; Warner & Norwood, 1991; Britton & Johnston, 1993). The children are bombarded with stimuli such as painful procedures, bright lights and sounds and yet deprived of sensations such as normal contact with their parents and families.…”
Section: Resultsmentioning
confidence: 99%
“…A number of parents came to resent the ‘ownership’ some nurses assumed of their children. Warner & Norwood (1991) found that the ‘ownership’ behaviour exhibited by nurses was frequently inadvertent but none the less very hurtful for parents.…”
Section: Resultsmentioning
confidence: 99%